2022
DOI: 10.1177/01945998211069505
|View full text |Cite
|
Sign up to set email alerts
|

Graduating Otolaryngology Residents’ Ideal Practice Expectations: A Longitudinal Analysis

Abstract: Objective Prior literature has indicated that the number of trained otolaryngologists required to meet the need of our growing population may be insufficient. Therefore, identifying trends in the subspecialty composition of future otolaryngology practices will elucidate workforce needs. Study Design One-page anonymous questionnaire. Setting The survey was completed by examinees at the conclusion of their American Board of Otolaryngology–Head and Neck Surgery oral examination from 2011 to 2019. Methods Data inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…H&N physicians whose scope of practice includes a substantial amount of general otolaryngology and those who do not work with residents reported significantly lower agreement scores with job alignment and job satisfaction. Miller et al 3 found that only 19% of all newly fellowship-trained otolaryngologists, including H&N oncologists, planned to include general otolaryngology as part of their practice. However, because of the need to build up a patient base early on and the relatively low reimbursement rates in providing H&N oncologic care, 8 treating general otolaryngology patients may be necessary for young H&N physicians despite the desire to care exclusively for patients with H&N cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…H&N physicians whose scope of practice includes a substantial amount of general otolaryngology and those who do not work with residents reported significantly lower agreement scores with job alignment and job satisfaction. Miller et al 3 found that only 19% of all newly fellowship-trained otolaryngologists, including H&N oncologists, planned to include general otolaryngology as part of their practice. However, because of the need to build up a patient base early on and the relatively low reimbursement rates in providing H&N oncologic care, 8 treating general otolaryngology patients may be necessary for young H&N physicians despite the desire to care exclusively for patients with H&N cancer.…”
Section: Discussionmentioning
confidence: 99%
“…About 58% to 64% of fifth-year otolaryngology residents anticipate advanced training following graduation, and about 13% to 18% of fifth-year residents expect to complete a fellowship in H&N and/or microvascular surgery. 3 , 4 However, for the newly graduated H&N oncology fellow in the current economic climate, there are uncertainties regarding the job application process and career expectations. While most H&N fellowship graduates tend to prefer a career in the academic setting over private practice, 4 this may not be an entirely realistic outcome if there is a limited number of academic positions available.…”
mentioning
confidence: 99%
See 1 more Smart Citation